Comparison Between the Use of 10% Lidocaine Spray on the Mole Palate, Posterior Pharynx, Tonsillar Pillar, Hypopharynx, and Endotracheal Tube on Hemodynamics and Post-Intubation Throat Pain - Wicaksono, Desmiko Haryo; Hamdi, Tasrif; Amelia, Rina; Ihsan, Mhd (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Intubation causes various side effects such as pain and parasympathetic stimulation, hemodynamic changes, increased intracranial pressure, and increased risk of intracranial hemorrhage. Topical lidocaine has been applied for decades via intratracheal spray, oxygen atomization, intracuff filling, or gel lubrication due to its advantages in simplicity of operation. Topical lidocaine is one of the drugs of choice to prevent post-intubation sore throat by decreasing the permeability of nerve membrane cells to sodium ions.Objective: To determine the relationship between the use of 10% lidocaine spray on the mole palate, posterior pharynx, tonsillar pillar, hypopharynx, and endotracheal tube on hemodynamics and post-intubation throat pain.Methods: This study employed a single-blind, randomized clinical trial design with 17 research subjects per group. Group A was given xylocaine spray on the endotracheal tube, and 17 subjects belonging to group B were given xylocaine spray on the soft palate, hypopharynx, and tonsil pillars.Result: Mean arterial pressure in this study in group A was found to be 91.11 + 6.55 and in group B 91.11 + 6.55, for post-operative sore throat (POST) scores in group A 0.51 + 0.26 and for group B 1.21 + 0.13.Conclusion: There is a difference between the use of 10% lidocaine spray on the soft palate, posterior pharynx, tonsillar pillars, hypopharynx, and endotracheal tube on hemodynamics and the incidence of sore throat after endotracheal intubation in elective patients with general anesthesia at RS Adam Malik, Medan.